(untitled) (Journal of the College of Education for Women, 2019)
AbstractThis study aims to evaluated the user satisfaction of retrieval servicesconcerning to universities thesis and dissertations in university dissertationunit of Baghdad Library for achieving the following objectives:1- Evaluating the performance of this unit (thesis unit of Baghdad UniversityLibrary) regarding to users opinion.2- Recognizing the reasons in this unit behind the case of non satisfaction ofits users and trying to find the suitable solutions.To achieve those two objectives, the questionnaire tool was performedand determined the user’s satisfaction level by using a sample survey. 1118graduated students were subjected to this experiment. The following mainresults were appeared:§ The satisfaction level of the service was 77% for Ph.D. students, and 82%for M.Sc students, those two percentage rates were considered are goodfor this service.§ The non satisfaction reasons for this service could be assigned intofollowing :- Non conformance the language of users and the system language.- There are many thesis and dissertations which related to users need butdid not retrieved by the system.This study instructed the following:v Improving the retrieval system particularly which it is related to the subjectanalysis to make the system language mach with the user language.v Data Base should be established for all of those university thesis anddissertations and it must be accessible on the internet.